O currículo em escolas quilombolas do Paraná: a possibilidade de um modo de ser, ver e dialogar com o mundo - Ferreira, Antônio (2014)
This thesis aims to investigate how the school reflects the worldviews of Quilombola s communities into the school curriculum. The social relevance of this work comes from the understanding that we are the country of ethnic and cultural diversity. However, there is a portion of the population whose social reality is still partly historically invisible to policy makers and Academia. The hypothesis that is examined here is that the curriculum in these Quilombolas schools in Paraná represses the voice of the Quilombola s people, makes their traditional knowledge a folklore and ignores the social dynamics of these communities. The survey had three main investigative steps to focus the view of the researcher about the defined problem: documentary, bibliographical and fieldwork. This does not mean that they were made sequentially and in a stratified way but simultaneously, as the object of study is revealed in its totality and complexity, requiring from the researcher a careful and systematic look. The methodological work was the ethnographic qualitative study in order to choose the descriptive and analytical work, so that it was possible to identify the causes that lead to the hiding of Quilombola s knowledge in the school curriculum. The theoretical bases for this dissertation were sought at Arruti, Bhabha GEERTZ, HALL, SACRISTÁN, Santomè, Munanga, among others, that allowed us to study the field and analyze how the traditional knowledge of Quilombola s community is included in the school curriculum. The results indicate that the curriculum of the two Quilombola s schools surveyed represses the voice of Quilombola s people, makes their traditional knowledge a folklore, ignores the social dynamics of these communities and reveals the perception of Quilombola s leaders that the Quilombola s school belongs to the Quilombola s community